[PP.06.06] PHENOTYPES OF BLOOD PRESSURE IN PATIENTS WITH RHEUMATOID ARTHRITIS. (September 2017) - Velmakin, S.; Troitskaya, E.; Villevalde, S.; Kobalava, Z.
Abstract : Objective: Patients with rheumatoid arthritis (RA) have increased cardiovascular risk. Arterial hypertension (AH) is highly prevalent, and seems to be under-diagnosed and under-treated among patients with RA. Data on ABPM profile in patients with rheumatoid arthritis are lacking. The aim of the study was to evaluate ABPM parameters and characterize phenotypes of blood pressure (BP) in patients with RA. Design and method: 58 patients with RA (EULAR 2010) without known cardio-vascular disease were examined (76% females, age 55, 9 ± 15, 8 (M ± SD) years, 10% smokers, 56% with AH, 34% with dyslipidemia). Median duration of RA was 8, 5 years (IQR 3–16). Seropositive RA was diagnosed in 69% of patients. All patients received disease-modifying antirheumatic drugs (DMARDs), 22 (38%) - biological treatment. Median duration of AH was 4, 0 years (IQR 0–12 years). All patients with AH received antihypertensive treatment. 24-h peripheral and central BP monitoring was performed (BPLab Vasotens, «Petr Telegin»). P < 0.05 was considered significant. Results: Mean office BP was 126 ± 19/78 ± 11 mmHg (peripheral) and 118 ± 20/80 ± 11 mmHg (central). 10 (17%) patients had elevated office BP (>140/90 mmHg). Mean BP values for peripheral and central BP were as follows: 125 ± 13/73 ± 9 and 116 ± 13/75 ± 9 mmHg for 24-h BP; 127 ± 14/74 ± 9 and 117 ± 13/77 ± 9 mmHg for daytime BP; 119 ± 13/69 ± 10 and 112 ± 14/71 ± 10 mmHg for nighttime BP. AH according to daytime BP was found in 14 (24, 1%) pts, nighttime BP – in 28 (48, 3%) pts, 24-h BP - in 9 (31, 0%) pts. Phenotypes of BP were as follows: sustained normotension – in 36 (62, 1%), masked hypertension in 12 (20, 7%), sustained AH – in 8 (13, 8%), white-coat hypertension in 2 (3, 4%) patients. Isolated nocturnal AH was observed in 12 (20, 7%) pts. 10 (17%) patients had isolated elevated central BP. 20 (34, 5%) pts had elevated central SBP according to individual reference values; all patients with high office BP had elevated central BP. Conclusions: High prevalence of AH is observed in patients with RA free of CVD and most of patients have satisfactory control of office BP. Relatively high prevalence of masked and isolated nocturnal hypertension despite antihypertensive treatment are observed in this population. These findings may help to optimize hypertension treatment in patients with RA.